Individual variation, personality, and the ability of animals to cope with climate change - Cockrem, John F. (Frontiers in Ecology and Evolution, 2022)
The Sixth Assessment of the Intergovernmental Panel on Climate Change describes negative effects of climate change on animals occurring on a larger scale than previously appreciated. Animal species are increasingly experiencing more frequent and extreme weather in comparison with conditions in which the species evolved. Individual variation in behavioural and physiological responses of animals to stimuli from the environment is ubiquitous across all species. Populations with relatively high levels of individual variation are more likely to be able to survive in a range of environmental conditions and cope with climate change than populations with low levels of variation. Behavioural and physiological responses are linked in animals, and personality can be defined as consistent individual behavioural and physiological responses of animals to changes in their immediate environment. Glucocorticoids (cortisol and corticosterone) are hormones that, in addition to metabolic roles, are released when the neuroendocrine stress system is activated in response to stimuli from the environment perceived to be threatening. The size of a glucocorticoid response of an animal is an indication of the animal’s personality. Animals with reactive personalities have relatively high glucocorticoid responses, are relatively slow and thorough to explore new situations, and are more flexible and able to cope with changing or unpredictable conditions than animals with proactive personalities. Animals with reactive personalities are likely to be better able to cope with environmental changes due to climate change than animals with proactive personalities. A reaction norm shows the relationship between phenotype and environmental conditions, with the slope of a reaction norm for an individual animal a measure of phenotypic plasticity. If reaction norm slopes are not parallel, there is individual variation in plasticity. Populations with relatively high individual variation in plasticity of reaction norms will have more animals that can adjust to a new situation than populations with little variation in plasticity, so are more likely to persist as environments change due to climate change. Future studies of individual variation in plasticity of responses to changing environments will help understanding of how populations of animals may be able to cope with climate change.